Analysis Thermal for Disc Brake Using Finite Element Analysis (FEA) - Alparis Nico Putra Utama; Wanda Afnison; Delima Yanti sari; Rifelino Rifelino (Unversitas Negeri Padang, 2025)
Traffic accidents are one of the highest causes of death in Indonesia. One of the factors traffic accidents is caused by vehicles, in this case the braking system. Brakes are a device on a vehicle that functions to reduce the speed by applying friction. The main feature in the braking system is heat dissipation. If the brake overheating, the effectiveness of the braking system will be reduced. In general, there are two types of brakes, but in modern vehicles disc brake more used. In this study, various types of disc brakes will be tested. The designs tested are solid disc brakes, drilled-type disc brakes, and grooved-type disc brakes. The aim of research for determine the most optimal disc brake design. The temperature value on the surface of the disc brake will be measure. The Finite Element Analysis (FEA) method is used in this study. The validation process is carried out by comparing analytical result and Finite Element Analysis result on solid disc brakes. The speed before braking is 60 km / h. Material used on disc brake is grey cast iron. In the simulation process using Finite Element Analysis, the mesh size used is 3 mm and the number of elements is 255,244 elements. After the analysis was carried out, the temperature value in the grooved-type disc brake design was the smallest value than another with a maximum temperature of 143.56 ºC during braking. Thus, based on the results obtained, the grooved-type disc brake tends to be more optimal.